Segurança pública e inefetividade estatal: o direito fundamental à segurança pessoal a partir da reflexão sobre o direito de possuir e portar arma de fogo - Netto, Estácio Luiz Gama de Lima (2017)
The research analyzes the problem of the legal prohibition of access to firearms by ordinary Brazilian citizens, seeking the reasons why the Brazilian State opted for the politics of disarmament. It is noted that the policy of disarming the civil population is entangled in a much larger package, which involves analyzing the role of the State in society, considering its power to intervene in individual freedom as a danger that always requires skepticism, prudence and resistance. Any public policy that essentially interferes in the individual freedom of citizens has costs, more negative than positive. The case of disarmament is even more sensitive because it is directly linked to the fundamental right to life and its most cruel violation, namely homicide. Thus, Laws such as 9.437/97 and 10.826/03 - the Disarmament Statute - are contextualized in this cultural, juridical and political context, demonstrating that in addition to the discourse of peace and the reduction of crime and violence, these Laws have only brought more insecurity and social vulnerability. It argues, therefore, for a change not only in interpreting the fundamental right to security, focusing on the analysis of the personal bias of this right, but also legislative, with the analysis of bill 3.722/12.